A randomised controlled trial and cost-consequence analysis of traditional and digital foot orthoses supply chains in a National Health Service setting: application to feet at risk of diabetic plantar ulceration - D. J. Parker; G. H. Nuttall; N. Bray; T. Hugill; A. Martinez-Santos; R. T. Edwards; C. Nester (Journal of Foot and Ankle Research, 2019)
Abstract Background Diabetic foot ulceration is a considerable cost to the NHS and foot orthotic provision is a core strategy for the management of the people with diabetes and a moderate to high risk of foot ulceration. The traditional process to produce a custom-made foot orthotic device is to use manual casting of foot shape and physical moulding of orthoses materials. Parts of this process can be undertaken using digital tools rather than manual processes with potential advantages. The aim of this trial was to provide the first comparison of a traditional orthoses supply chain to a digital supply chain over a 6 month period. The trial used plantar pressure, health status, and health service time and cost data to compare the two supply chains. Methods Fifty-seven participants with diabetes were randomly allocated to each supply chain. Plantar pressure data and health status (EQ5D, ICECAP) was assessed at point of supply and at six-months. The costs for orthoses and clinical services accessed by participants were assessed over the 6 months of the trial. Primary outcomes were: reduction in peak plantar pressure at the site of highest pressure, assessed for non-inferiority to current care. Secondary outcomes were: reduction in plantar pressure at foot regions identified as at risk (> 200 kPa), cost-consequence analysis (supply chain, clinician time, service use) and health status. Results At point of supply pressure reduction for the digital supply chain was non-inferior to a predefined margin and superior (p < 0.1) to the traditional supply chain, but both supply chains were inferior to the margin after 6 months. Custom-made orthoses significantly reduced pressure for at risk regions compared to a flat control (traditional − 13.85%, digital − 20.52%). The digital supply chain was more expensive (+£13.17) and required more clinician time (+ 35 min). There were no significant differences in health status or service use between supply chains. Conclusions Custom made foot orthoses reduce pressure as expected. Given some assumptions about the cost models we used, the supply chain process adopted to produce the orthoses seems to have marginal impact on overall costs and health status. Trial registration Retrospectively registered on ISRCTN registry (ISRCTN10978940, 04/11/2015).